Pengaruh Partisipasi Anggaran dan Komitmen Organisasi Terhadap Budgetary Slack - Mamentu, Ezra; Carolina, Yenni (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
This study aims to examine the effect of budgetary participation and organizational commitment on budgetary slack which is the basis of this research, namely the existence of ambiguous theoretical contradictions from several previous studies. The samples obtained were 45 people. For data acquisition, namely by distributing questionnaires to all respondents. The method used to analyze the data is multiple linear analysis. The results in this study state that budgetary participation and organizational commitment have a positive and significant impact on budgetary slack. The coefficient of determination is 63.5%, where variations in changes in budgetary slack can be explained by budgetary participation and organizational commitment variables, while the remaining 36.5% is explained by several other reasons outside the model.